(untitled) (Swiss Medical Weekly, 2024)
AIMS OF THE STUDY: To standardise the assessment of infants with fractures at University Children’s Hospital Zurich, a guideline was implemented in February 2021. The aim of this study was to assess adherence to this guideline and to assess changes in management before and after guideline implementation. The primary outcome was the overall adherence rate to the guideline. Additionally, we evaluated specific omissions of guideline steps by clinicians and investigated differences in adherence for infants younger vs older than six months, as well as variations between in- and outpatient care. Secondary outcomes focused on changes in the frequency of involvement of the child protection team, skeletal survey rates and child abuse detection, comparing these rates before and after guideline implementation. METHODS: We conducted a retrospective single-centre quality control study. We included infants younger than 12 months diagnosed with fractures at the emergency department between 1 February 2021 and 31 August 2022. We excluded children with prior bone disease diagnoses and those whose parents did not consent to their children’s data being used for research. RESULTS: A total of 61 emergency department visits of infants with fractures were included in the study. The overall adherence rate to the guideline was 39%. Notably, in 68% of cases where clinicians deviated from the guideline, the primary reason was a missing consultation of the paediatrician or family doctor. Adherence levels were consistent across age groups (under and over six months), but there was a notable discrepancy between inpatient (53%) and outpatient (26%) care settings. Child protection team involvement increased to 54%, twice the rate observed before guideline implementation. CONCLUSIONS: Overall adherence to the guideline was poor, emphasising the necessity for continuous training of clinicians to raise awareness regarding the differential diagnosis of child abuse. Despite the guideline’s implementation leading to a doubled rate of child protection team involvement, there remains a need for improvement. Notably, outpatient care exhibited lower guideline adherence, signalling an area requiring focused attention.